Differential Distributions of Synechococcus Subgroups Across the California Current System - Paerl, Ryan W.; Johnson, Kenneth S.; Welsh, Rory M.; Worden, Alexandra Z.; Chavez, Francisco P.; Zehr, Jonathan P. (Frontiers in Microbiology, 2011)
Synechococcus is an abundant marine cyanobacterial genus composed of different populations that vary physiologically. Synechococcus narB gene sequences (encoding for nitrate reductase in cyanobacteria) obtained previously from isolates and the environment (e.g. North Pacific Gyre Station ALOHA, Hawaii or Monterey Bay, California) were used to develop quantitative PCR (qPCR) assays. These qPCR assays were used to quantify populations from specific narB phylogenetic clades across the California Current System (CCS), a region composed of dynamic zones between a coastal-upwelling zone and the oligotrophic Pacific Ocean. Targeted populations (narB subgroups) had different biogeographic patterns across the CCS, which appear to be driven by environmental conditions. Subgroups C_C1, D_C1 and D_C2 were abundant in coastal-upwelling to coastal-transition zone waters with relatively high to intermediate ammonium, nitrate and chl. a concentrations. Subgroups A_C1 and F_C1 were most abundant in coastal-transition zone waters with intermediate nutrient concentrations. E_O1 and G_O1 were most abundant at different depths of oligotrophic open-ocean waters (either in the upper mixed layer or just below). E_O1, A_C1 and F_C1 distributions differed from other narB subgroups and likely possess unique ecologies enabling them to be most abundant in waters between coastal and open-ocean waters. Different CCS zones possessed distinct Synechococcus communities. Core California Current (CC) water possessed low numbers of narB subgroups relative to counted Synechococcus cells, and coastal-transition waters contained high abundances of Synechococcus cells and total number of narB subgroups. The presented biogeographic data provides insight on the distributions and ecologies of Synechococcus present in an eastern boundary current system.